1997
DOI: 10.1017/s0813483900003557
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Children and Young Adults with Mental Retardation in School Programs: Current Research

Abstract: This paper reviews the recent behavioural research on instruction of children and young adults with mental retardation in schools settings and community-based school programs. Instructional research in 12 skill areas (motor, self-care, communication, social skills, choice making, school behaviours, health and safety skills, home management, leisure skills, community use, vocational skills, and academics) meeting specified criteria on population (age and disability), location of instruction, functionality of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…The right to make one's own decisions about life and future is viewed as an inalienable right by American adults without disabilities and yet has only recently been recognized for adults with disabilities (Wehmeyer, Palmer, Agran, Mithaug, & Martin, 2000). Evidence of this belated recognition is present in key pieces of disability legislation which have been passed or reauthorized since 1990 including the Americans With Disabilities Act of 1990, the Individuals with Disabilities Education Act, 1990 and1997, and the Reha-bilitation Act Amendments of 1992 (Ysseldyke, Algozzine, & Thurlow, 2000). These laws have all stressed the right of individuals with disabilities to choose where and with whom they want to live, what jobs they want, and by what means they want to achieve their personal goals and dreams.…”
mentioning
confidence: 99%
“…The right to make one's own decisions about life and future is viewed as an inalienable right by American adults without disabilities and yet has only recently been recognized for adults with disabilities (Wehmeyer, Palmer, Agran, Mithaug, & Martin, 2000). Evidence of this belated recognition is present in key pieces of disability legislation which have been passed or reauthorized since 1990 including the Americans With Disabilities Act of 1990, the Individuals with Disabilities Education Act, 1990 and1997, and the Reha-bilitation Act Amendments of 1992 (Ysseldyke, Algozzine, & Thurlow, 2000). These laws have all stressed the right of individuals with disabilities to choose where and with whom they want to live, what jobs they want, and by what means they want to achieve their personal goals and dreams.…”
mentioning
confidence: 99%
“…There have been a number of notable contributions to this end, all of which have focused on particular aspects of published intervention articles. For example, Snell (1997) provided a detailed review of instructional research with children and young adults with mental retardation between 1990 and 1996, and Dunlap and Childs (1996) offered a quantitative analysis of the intervention research in emotional and behavioral disorders between 1980 and 1993. Carr et al (in press) accumulated an exhaustive study of the research in positive behavioral support between 1985 and 1996, and Scotti and his colleagues have conducted meta-analyses of the behavioral support literature (Scotti, Evans, Meyer, & Walker, 1991; Ujcich, Weigle, Holland, & Kirk, 1996).…”
mentioning
confidence: 99%
“…One challenge in alternate assessments has been the incorporation of scientifically based research surrounding best practices for teaching academic skills to students with SCD. The research conducted by Snell [15] revealed that there is minimal guidance for educators to teach reading, math, and science skills to students with SCD, but there is considerable research related to teaching functional life skills. In order for students with SCD to become college, career, and community ready, they must become proficient in academic skills also.…”
Section: Review Of Literaturementioning
confidence: 99%